Implementasi Layanan Bimbingan Karir Dalam Menetapkan Jurusan di SMA Muhammadiyah 6 Palembang - Kusuma, Arian; Ferdiansyah, M; Arizon, Arizon (ANTHOR: Education and Learning Journal, 2022)
This research has a goal, namely to encourage or help students determine the direction of cross-interest subject groups and subject-depth groups to be pursued according to the talents and interests of students so that students can determine their career choices and further study options. The method used in this research is the descriptive qualitative method. The sources of data obtained in this study are interviews, and documents on career guidance and counseling services in the guidance and counseling room for students at Muhammadiyah 6 Palembang High School for the 2021/2022 academic year in Palembang City. Data collection in this study used documentation, interviews, and observations. The data analysis technique used is an interview and observation technique. The results of research conducted by researchers regarding the implementation of career guidance services in determining majors at SMA Muhammadiyah 6 Palembang show good and enthusiastic results. Most of the students who were given this service said they felt helped in determining their further education careers and were motivated to achieve their goals. Likewise BK teachers provide grateful services because with this research students can further explore knowledge about further education, especially for students who are usually passive to be active to help students in determining their respective further education decisions.